A comparative study to assess efficacy of Tzanakis score and Alvarado score for effective diagnosis of patients with acute appendicitis at a tertiary care centre in North Karnataka: a one-year prospective analytical study - Sharma, Dron; Koujalagi, R. S. (International Surgery Journal, 2020)
Background: Acute appendicitis standout amongst the most widely recognized reasons for intense stomach torment. There is no ideal symptomatic assessment apparatus to distinguish acute appendix if indications are ambiguous, bringing about longer analytic procedure and it might prompt deferring of medical procedure and related increment in morbidity and fatality. In the meantime, speedy management may prompt negative appendectomy with expanded morbidity and consumption of healthcare resources. Methods: A Hospital based one year prospective study was conducted at KLEs Dr Prabhakar Kore Hospital Belagavi, Karnataka from 1st January 2018 to 31st December 2018 and required data was collected from 100 patient who were clinically diagnosed to have acute appendicitis and all patients were assessed using Alvarado score and Tzanakis score and HPR for all patients were used as gold standard to evaluate the efficacy of both scoring systems. Results: The sensitivity and specificity of Tzanakis score was 80.6% (at score >8) and 100% (at score >8) respectively. positive predictive value in present study being 100% and negative predictive value being 41.3%. The sensitivity and specificity of Alvarado score was 11.3% (at score >8) and 100% (at score >8) respectively. Conclusions: Tzanakis Score outperformed Alvarado score displaying higher sensitivity with similar specificity.